Protective action of N-acetyl-L-cysteine associated with a polyvalent antivenom on the envenomation induced by Lachesis muta muta (South American bushmaster) in rats. (30th July 2021) - Leão-Torres, Aline G.; Pires, Carina V.; Ribelato, Amanda C.; Zerbinatti, Maria C.; Santarém, Cecília L.; Nogueira, Rosa M.B.; Giometti, Inês C.; Giuffrida, Rogério; Silva, Elisangela O.; Gerez, Juliana R.; Silva, Nelson J.; Rowan, Edward G.; et al.
Abstract: In this study, we examined the potential use of N -acetyl-L-cysteine (NAC) in association with a polyvalent antivenom and as stand-alone therapy to reduce the acute local and systemic effects induced by Lachesis muta muta venom in rats. Male Wistar rats (300–350 g) were exposed to L. m. muta venom (1.5 mg/kg – i.m.) and subsequently treated with anti- Bothrops / Lachesis serum (antivenom:venom ratio 1:3 'v/w' – i.p.) and NAC (150 mg/kg – i.p.) separately or in association; the animals were monitored for 120 min to assess changes in temperature, locomotor activity, local oedema formation and the prevalence of haemorrhaging. After this time, animals were anesthetized in order to collect blood samples through intracardiac puncture and then euthanized for collecting tissue samples; the hematological-biochemical and histopathological analyses were performed through conventional methods. L. m. muta venom produced pronounced local oedema, subcutaneous haemorrhage and myonecrosis, with both antivenom and NAC successfully reducing the extent of the myonecrotic lesion when individually administered; their association also prevented the occurrence of subcutaneous haemorrhage. Venom-induced creatine kinase (CK) release was significantly prevented by NAC alone or in combination with antivenom; NAC alone failed to reduce the release of hepatotoxic (alanine aminotransferase) and nephrotoxic (creatinine) serum biomarkers induced by L. m. muta venom. Venom induced significant increase of leucocytes which was also associated with an increase of neutrophils, eosinophils and monocytes; antivenom and NAC partially reduced these alterations, with NAC alone significantly preventing the increase of eosinophils whereas neither NAC or antivenom prevented the increase in monocytes. Venom did not induce changes in the erythrogram parameters. In the absence of a suitable antivenom, NAC has the potential to reduce a number of local and systemic effects caused by L. m. muta venom. Graphical abstract: Image 1 Highlights: Lachesis muta muta venom induces potent acute local and systemic toxicity. N -acetyl-L-cysteine prevents the venom-induced local and systemic myotoxicity. N -acetyl-L-cysteine attenuates the venom-induced inflammatory response. N -acetyl-L-cysteine prevents the venom-induced skeletal muscle, hepatic and renal tissue damage. N -acetyl-L-cysteine has therapeutic potential to be used in the absence of a suitable antivenom.